Analysis for Frictional Heat Generation Characteristic of Machine Tool Spindle Bearing - Hao Yu; Dongchen Qin; Jiangyi Chen; Feng Yuan (Jixie chuandong)
In order to study the frictional heat generation characteristics of cylindrical roller bearings，taking the effect of the initial assembly interference between the shaft and bearings，the centrifugal force and mating surface roughness into account， a quasi-static analysis model considering is established. With the local heat source method， the frictional heat generation amount between the components of the bearing is calculated， and the effects of different working conditions and lubrication parameters on the frictional heat generation are analyzed through an example. Results show that the rotation speed and the external load have a great impact on the frictional heat generation amount. When the rotation speed is high，the growth of the frictional heat generation amount is obvious. The increase of the lubricating oil dynamic viscosity or the oil-air proportional coefficient will both make the frictional heat generation amount show a trend of increasing.